Developing Learners’ Self-Assessment Accuracy in Reading Skills and Strategies - Azizmalayeri, Faramarz (2008)
Self-assessment is one example of what is currently called alternative assessment. Alternative assessment procedures are often developed in an attempt to make testing and assessment more responsive and accountable to individual learners, to promote learning, and to enhance ethic and equality in education (McNamara, 1998). Attempts have been made to ensure validity and to establish credibility for self assessment as an alternative assessment. The currently in-use self assessment instrument maintains ‘can-do statements’ which are developed based on the ACTFL. The new guidelines by the Council of Europe (2001) are intended to be used as references for languages called The Common European Framework for References (CEFR). The utilized self assessment instrument in this research is CEFR-based officially developed. The purpose of this study is to empirically investigate the effects of training students taking self assessment checklist and reflecting to the reading proficiency benchmarks. The learners’ accuracy with self assessment is investigated across an intensive period of training. The TESL students have been trained for a whole semester taking the CEFR-based self assessment of reading skills. There are four specific objectives for this study: 1) to investigate the accuracy of self assessment results, 2) to determine the optimal training period, 3) to estimate the maximum correlation between the CEFR-based self assessment instrument and an established measure of reading proficiency (TOEFL), and 4) to probe into the quality of improvement and change in learners’ perceptions, understanding and internalization of the CEFR benchmarks. In order to meet the above objectives, four research questions were asked. The research design utilized is mixed-method quasi-experimental design in which qualitative findings triangulate the quantitative results. A class of semester 7 TESL students, as a whole intact group, attended a semester training period. They were tested for their current reading proficiency using the TOEFL reading test battery. Meanwhile, they attempted the CEFR-based self assessment checklist of reading skills three times across the training period. These two measures were used for the purpose of the statistical analyses. Repeated Measures Two-Way ANOVA and Multiple Regression were used to test the hypotheses. It was found out that the provided training has been effective as the student’s results were more accurate in the second and the third administrations of the self assessment compared to the first attempt (large Effect Size, η2 = .185, p<.05). The results of the Stepwise Multiple Regression Analysis revealed that among the three administrations of the self assessment instrument, the second and the third administrations explained 79% of the observed variation in the dependent variable together; therefore, the adopted model included the second and the third administrations. The Correlation Coefficients in the Correlation Matrix depicts that the third administration of the self assessment instrument is highly correlated with the external proficiency measure (TOEFL) (r = .88, p<.05). The qualitative inquiry revealed that students are apt to achieve self assessment autonomy and acquire the ability to self assess via intensive training. Therefore, as the result of training students taking self assessment of reading, their results are more accurate and dependable.